Genome Variation Map: a worldwide collection of genome variations across multiple species. Issue Volume 49:Issue D1(2021) (10th November 2020) - Li, Cuiping; Tian, Dongmei; Tang, Bixia; Liu, Xiaonan; Teng, Xufei; Zhao, Wenming; Zhang, Zhang; Song, Shuhui
Abstract: The Genome Variation Map (GVM; http://bigd.big.ac.cn/gvm/ ) is a public data repository of genome variations. It aims to collect and integrate genome variations for a wide range of species, accepts submissions of different variation types from all over the world and provides free open access to all publicly available data in support of worldwide research activities. Compared with the previous version, particularly, a total of 22 species, 115 projects, 55 935 samples, 463 429 609 variants, 66 220 associations and 56 submissions (as of 7 September 2020) were newly added in the current version of GVM. In the current release, GVM houses a total of ∼960 million variants from 41 species, including 13 animals, 25 plants and 3 viruses. Moreover, it incorporates 64 819 individual genotypes and 260 393 manually curated high-quality genotype-to-phenotype associations. Since its inception, GVM has archived genomic variation data of 43 754 samples submitted by worldwide users and served >1 million data download requests. Collectively, as a core resource in the National Genomics Data Center, GVM provides valuable genome variations for a diversity of species and thus plays an important role in both functional genomics studies and molecular breeding.